Desenvolvimento de métodos rápidos de análise de fáimacos por eletroforese capilar com detecção condutométrica sem contato (CE-G4D) - Ribeiro, Michelle Miranda Araújo de Carvalho (2017)
This work presents three new analytical procedures for rapid and simultaneous determination of: (i) diphenhydramine (DIF), pyridoxine (PIR) and 8 -chlorotheophylline (CTF) (t <3 min); (ii) naphazoline (NAF), and zinc (Zn) (t <41 s); (iii) NAF associated with DIF or pheniramine (FEN) or chlorpheniramine (CFEN) (t <35 s) by capillar y electrophoresis with contactless capacitive coupled conductivity detection (CE-C4D). The proposed methods can be used in quality control of raw materials and pharmaceutical formulations having such compounds in its composition. Therefore, three different methods were developed: for simultaneous determination of group (i), the BGE was composed by 20 mmolL-1 of boric acid and 25 mmol L-1 NaOH (pH = 9.0). The limits of detection (LOD) was 0.6, 1.3 and 1.3 pmol L-1 for DIF, PIR and CTF, respectively. The method was accurate with recovery values between 98 and 100%. For simultaneous determination of group (ii), the BGE was composed by HIS/MES (20 mmol L-1 each) (pH = 6.0). The LODs were 20 and 30 pmol L-1 for NAF and Zn, respectively. The method presented recovery values between 97 and 102%. For simultaneous determination of group (iii), the BGE was composed by HIS 20 mmol L-1 + DMX 10 mmol L-1 + 1 mmol L-1 de NaOH (pH = 9.8). The LODs were 25 pmol L-1 for NAF, DIF and FEN and 13 pmol L-1 for CFEN. The recovery values were between 94 and 101%. Calibration curves for all species showed correlation coefficients greater than 0.996 and RSD values less than 3.5% (n = 10). The results obtained with the proposed methods were statistically similar (confidence level of 95%) to those obtained by HPLC (organic compounds) and FAAS (Zn). Furthermore, the CE-C4D methods are simple, generates a minimum amount of waste (lower environmental impact), are low cost (equipment and maintenance) and has a high analytical frequency: ~21 injections h-1 (i) ~90 injections h-1 (ii) and ~115 injections h-1 (iii).